JARINGAN INTELEKTUAL ABDURRAUF AS-SINGKILI DALAM PENYEBARAN ISLAM DI ACEH ABAD KE-17 - Muhammad Yandi; Redho Rahmatullah; Nurzena (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the intellectual network of Abdurrauf As-Singkili in the efforts to spread Islam in Aceh in the 17th century and his contribution to the development of Islamic scientific traditions in the region. The study focuses on the process of knowledge transmission, intellectual relations with institutions and scholars in Islamic educational centers in the Middle East, and his role in shaping religious legitimacy in Aceh. The method used in this study is a qualitative approach with a historical method through library research, which utilizes various sources in the form of manuscripts, Abdurrauf As-Singkili's written works, historical documents, and related scientific literature. The research findings show that Abdurrauf As-Singkili's intellectual network was built through intense scientific interactions with scholars in Haramain during his education, which later became an important foundation in the spread and development of Islamic knowledge in Aceh. Through the writing of scientific works, da'wah activities, and teaching of tarekat, Abdurrauf made a significant contribution in strengthening the religious understanding of the community while shaping an Islamic character that was able to adapt to local social and cultural conditions. Furthermore, the existence of this intellectual network helped solidify Aceh's position as a center of Islamic development in the Indonesian archipelago in the 17th century. Therefore, Abdurrauf As-Singkili can be understood not only as a regional scholar but also as a key figure in the Islamic intellectual network in the Malay-Indonesian archipelago.